Pemikiran Abdullah An-Na`Im Tentang Teori Evolusi Syari`Ah (Nasakh) Dan Relevansinya Dengan Metode Istinbath Hukum Islam - Dwi Sagita Akbar; Afifi Fauzi Abbas (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2020)
In order to offer a transformative discourse Abdullah Ahmad An-Na'im build a method he called with the evolution of Shari'ah (abrogated). According to him the method can respond to contemporary issues at this time. Because he assumed that abrogating is one of the principal methods and has a wide and high complexity in theology and fiqh (jurisprudence) of Islam. He tries to deconstruct abrogated method and also some methods of ijtihad that had been considered settled by the classical scholar. Abdullah Ahmad An-Na'im radically have done repeated studies against the epistimologi Islamic law as well as the mereformulasi return and customize it with the standard of human rights as well as international law as a benchmark. The method developed by Abdullah Ahmad An-Na'im, he stated three important things that need to be done to realize the abrogating. Text, values of humanity, and logic. He also overestimated human rights, so that a text (paragraph) may be enforced in accordance with human rights. In order to answer the legal issues of contemporary Islam.